Endometrioza - Franko, Tjaša (Socialno delo, 2018)
The study addresses endometriosis, a frequently overlooked disease that affects women, and it is based on the development of critical social work which recognizes structures of oppression and privilege on social and individual level in the case of female reproductive health. The purpose of the research is to draw attention to social inequalities in the case of endometriosis, and to enable social work to open theoretical space for social work action and change, in order to increase the participation of the social work profession in health care. The author draws attention to the existing structural ratios of power, expressed on both legal and professional levels, and constructed on gender inequalities, misogyny and stereotypical behaviors.
Keywords: biomedicinska pomoč; diskriminacija; endometrioza; neenakost spolov; reprodukcija; reproduktivne pravice; zdravstvena oskrba; žensko zdravje